Zika virus and its clinical implications: a comprehensive review - Baid, Rashmi; Agarwal, Rakesh (International Journal of Research in Medical Sciences, 2017)
Recent Zika virus outbreak in Latin America and the Caribbean has drawn the world’s attention toward this relatively unknown virus, with WHO declaring it a public health emergency of international concern (PHEIC). India has had its own tryst with Zika virus with that “significant numbers” of Indians had already been exposed to Zika as early as 1950s. An exponential spread of Zika virus is a potential public health concern, with implications requiring immediate action. The devastating complications of Zika virus infection, particularly congenital and neurological, makes imperative a thorough, thoughtful, and level-headed public health approach in dealing with this infection especially during pregnancy. We review the data on this deadly infection in this brief review including its history, epidemiology, clinical features and management aspects particularly in pregnant women.